Self-cleaning high-strength and high-toughness geopolymer material suitable for fabricated pavement and preparation method of self-cleaning high-strength and high-toughness geopolymer material
By using raw materials such as slag, fly ash, etc. to prepare high-strength and high-toughness polymer materials with porous zeolite structures, the problems of insufficient strength and cleanliness of prefabricated pavement materials are solved, and efficient dust adsorption and improved traffic load tolerance are achieved, and the traffic load tolerance is improved. Lifespan and reduce maintenance costs.
Patent Information
- Application Number
- CN202411234163.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-07
AI Technical Summary
The strength and toughness of existing prefabricated pavement materials during use are difficult to meet the needs of traffic loads, and are prone to cracks and damage, and long-term exposure to the external environment leads to accumulation of dust and dirt and difficult to clean. Traditional cleaning methods consume a lot of manpower and material resources and have limited results.
Self-cleaning high-strength and high-tough polymer materials are prepared using raw materials such as slag, fly ash, alkali triggers, polyethylene fibers and high alumina cement. By generating porous zeolite structures, dust adsorption and gelling product filling are achieved to enhance the density of the material, forming High strength and high toughness material.
It significantly improves the performance of the road surface, can withstand heavier traffic loads, extends service life, realizes self-cleaning function, reduces maintenance costs and manual cleaning labor intensity, and is environmentally friendly in the preparation process, low cost, and is suitable for large-scale production.
Smart Images

Figure CN119263750A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and in particular relates to a self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement and a preparation method thereof. Background Art
[0002] With the rapid development of modern transportation, road construction is facing higher requirements and challenges. The traditional cast-in-place pavement construction method has many problems, such as long construction period, great interference with traffic, and difficult to control on-site construction quality. In this context, prefabricated pavement has emerged as an innovative solution.
[0003] In the construction of modern transportation infrastructure, prefabricated pavements have gradually gained attention due to their advantages such as efficient construction and easy quality control. However, existing prefabricated pavement materials face many challenges during use. On the one hand, the strength and toughness of conventional materials are often difficult to meet the growing traffic load requirements, and they are prone to cracks, breakage and other problems, affecting the service life and safety of the pavement. On the other hand, the accumulation of dust and dirt on the pavement after long-term exposure to the external environment has become a common and difficult problem to solve. Traditional cleaning methods not only consume a lot of manpower and material resources, but also have limited effects and are difficult to fundamentally solve the dust accumulation problem.
[0004] As a new type of building material, alkali-activated geopolymer material has good performance potential, but there are still some shortcomings in practical applications. Therefore, through the optimization and innovation of materials, the development of a prefabricated pavement material with both high strength and high toughness and self-cleaning function has become an important direction of current pavement material research. Therefore, how to provide a new structure of self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavement and its preparation method to solve or improve at least one of the above technical problems has a more realistic significance. Summary of the invention
[0005] The object of the present invention is to provide a self-cleaning high-strength and high-toughness geopolymer material of a new structure suitable for assembled pavement and a preparation method thereof, so as to solve or improve at least one technical problem existing in the related art.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is:
[0007] A self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement is prepared from the following raw materials in parts by weight: 20-25 parts of slag, 15-20 parts of fly ash, 6-8 parts of alkali activator, 8-12 parts of high-alumina cement, 2-5 parts of polyethylene fiber, and 15-20 parts of water.
[0008] As an improvement on the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the alkaline activator is selected from sodium hydroxide and water glass solution.
[0009] As an improvement on the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the purity of the sodium hydroxide is not less than 96%.
[0010] As an improvement on the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the modulus of the water glass solution is 1.5-3.5.
[0011] As an improvement on the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the fly ash needs to meet the requirements of fineness (45 μm square hole sieve residue) not more than 20% and loss on ignition not more than 8%.
[0012] As an improvement of the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the specific surface area of the slag is greater than 400m 2 / kg.
[0013] As an improvement on the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the activity index of the slag is not less than S95 grade.
[0014] As an improvement on the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavement, the high-alumina cement model is CA500-A700, the initial setting time is not earlier than 30 minutes, and the final setting time is not later than 6 hours.
[0015] As an improvement on the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, the polyethylene fiber has a length of 6-12 mm, a diameter of 20-40 μm, and a tensile strength of not less than 1000 MPa.
[0016] The self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements provided in the embodiments of the present invention (1) significantly improves pavement performance: the material of the present invention has high strength and high toughness characteristics, can withstand heavier traffic loads, reduce the occurrence of pavement cracks and damage, extend the service life of the pavement, and reduce maintenance costs. (2) Significant self-cleaning function: the porous zeolite structure generated can efficiently adsorb dust, so that the pavement can be kept clean for a long time, reducing the degradation of pavement performance and traffic safety hazards caused by dust accumulation, and also reducing the labor intensity and cost of manual cleaning. (3) Environmentally friendly: the preparation process of the material is relatively environmentally friendly, reducing the consumption of natural resources and pollution to the environment. (4) Economical and practical: the raw materials are widely available, the cost is relatively low, and the preparation process is simple, easy to mass produce and apply, which helps to reduce the construction cost of prefabricated pavements.
[0017] Another aspect of the present invention provides a method for preparing a self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, comprising the following steps:
[0018] (1) Raw material pretreatment: Dry the slag and fly ash separately to remove moisture and impurities to ensure the purity and quality of the raw materials. Prepare the water glass solution 24 hours in advance to release heat;
[0019] (2) Ingredients: accurately weigh slag, fly ash, alkali activator, high alumina cement and polyethylene fiber according to the above weight ratio;
[0020] (3) Dry mixing: Put slag, fly ash and polyethylene fiber into a mixer, stir and mix them thoroughly to form a dry mix;
[0021] (4) pulping: adding an alkali activator to an appropriate amount of water and stirring evenly to prepare an alkali activator solution;
[0022] (5) Wet mixing: slowly add the prepared alkali activator solution into the dry mix while continuously stirring to fully wet the material and form a uniform slurry;
[0023] (6) Adding high alumina cement: During the slurry stirring process, evenly add high alumina cement and continue stirring for a period of time to ensure that the high alumina cement is fully dispersed and participates in the reaction;
[0024] (7) Molding: Pour the evenly stirred slurry into a pre-prepared mold, vibrate and compact it, remove bubbles, and shape the material;
[0025] (8) Curing: The molded material is placed at room temperature for curing for 1 day, then demolded and moved to a steam curing box for curing at 80°C for 2 days.
[0026] Since the preparation method of the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements has the same inventive concept as the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements, the preparation method of the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements has all the technical effects of the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements, it will not be repeated here. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1It is a schematic diagram of a method for preparing a self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to one embodiment of the present invention. DETAILED DESCRIPTION
[0029] In the description of the present invention, it is to be understood that the terms “center”, “longitudinal”, “lateral”, “up”, “down”, “front”, “back”, “left”, “right”, “vertical”, “horizontal”, “top”, “bottom”, “inside”, “outside”, “axial”, “radial”, etc., indicating orientations or positional relationships are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is more than two, unless otherwise clearly and specifically defined.
[0031] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0032] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0033] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0034] The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided in the embodiment of the present invention comprises the following components and proportions by weight: 20-25 parts of slag, 15-20 parts of fly ash, 6-8 parts of alkali activator, 8-12 parts of high-aluminum cement, 2-5 parts of polyethylene fiber, and 15-20 parts of water. In other words, the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided in the embodiment of the present invention is made from the following raw materials by weight: 20-25 parts of slag, 15-20 parts of fly ash, 6-8 parts of alkali activator, 8-12 parts of high-aluminum cement, 2-5 parts of polyethylene fiber, and 15-20 parts of water.
[0035] In some embodiments of the present invention, the specific surface area of the slag is greater than 400m 2 / kg, and the activity index is not less than S95 level to enhance the durability and chemical corrosion resistance of the material.
[0036] In some embodiments of the present invention, the fly ash needs to meet the requirements of fineness (residue on a 45 μm square sieve) not exceeding 20% and loss on ignition not exceeding 8%, which helps to improve the working performance of the material and reduce costs.
[0037] In some embodiments of the present invention, the alkaline activator is selected from sodium hydroxide and water glass solution, the purity of sodium hydroxide is not less than 96%, and the modulus of the water glass solution is 1.5-3.5, which is used to stimulate the reaction of the geopolymer to form a high-strength structure.
[0038] In some embodiments of the present invention, the high-alumina cement model is CA500-A700, and the initial setting time of the high-alumina cement is required to be no earlier than 30 minutes, and the final setting time is no later than 6 hours. Zeolite is generated during the reaction process, giving the material self-cleaning properties. Therefore, the addition of high-alumina cement CA500-A700 will generate zeolite, which is porous and has a strong adsorption effect. It can absorb dust on the road surface.
[0039] In some embodiments of the present invention, the polyethylene fiber has a length of 6-12 mm, a diameter of 20-40 μm, and a tensile strength of not less than 1000 MPa, so as to significantly improve the toughness of the material.
[0040] It should be noted that in the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided in the embodiment of the present invention, on the one hand, high-alumina cement is rich in silicon and calcium, and reacts with other raw materials in an alkaline environment to form a crystal structure of zeolite (CaO·Al2O3·SiO2·H2O). The porous nature of zeolite is due to the presence of regularly arranged channels and voids in its crystal structure. These pores can provide a large number of adsorption sites. When dust particles contact the surface of the material, the dust is captured and fixed in the pores due to the effects of physical adsorption and chemical adsorption, thereby achieving a self-cleaning effect. On the other hand, slag and fly ash undergo hydration reactions under the action of an alkali activator, and the resulting gelled products fill the pores of the material, increasing the density of the material, thereby increasing the strength. The interfacial bonding force between the polyethylene fiber and the matrix can transfer stress. When the material is subjected to external force, the fiber can bear part of the tensile force, prevent the rapid development of cracks, and improve the toughness of the material. Therefore, the self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements provided by the embodiments of the present invention has the following technical effects: (1) Significantly improve pavement performance: The material of the present invention has high strength and high toughness characteristics, can withstand heavier traffic loads, reduce the occurrence of pavement cracks and damage, extend the service life of the pavement, and reduce maintenance costs. (2) Significant self-cleaning function: Through the generated porous zeolite structure, dust can be efficiently adsorbed to keep the pavement clean for a long time, reducing the degradation of pavement performance and traffic safety hazards caused by dust accumulation, and also reducing the labor intensity and cost of manual cleaning. (3) Environmentally friendly: The preparation process of the material is relatively environmentally friendly, reducing the consumption of natural resources and pollution to the environment. (4) Economical and practical: The raw materials are widely available and the cost is relatively low. The preparation process is simple and easy to mass produce and apply, which helps to reduce the construction cost of prefabricated pavements.
[0041] like Figure 1 As shown, the method for preparing the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided in an embodiment of the present invention comprises the following steps:
[0042] (1) Raw material pretreatment: Dry the slag and fly ash separately to remove moisture and impurities to ensure the purity and quality of the raw materials. Prepare the water glass solution 24 hours in advance to release heat.
[0043] (2) Ingredients: Accurately weigh slag, fly ash, alkali activator, high alumina cement and polyethylene fiber according to the above weight ratio.
[0044] (3) Dry mixing: Place slag, fly ash and polyethylene fiber into a mixer and mix thoroughly to form a dry mix.
[0045] (4) Pulping: Add the alkali activator into an appropriate amount of water and stir evenly to prepare an alkali activator solution.
[0046] (5) Wet mixing: Slowly add the prepared alkali activator solution into the dry mix while continuously stirring to fully wet the material and form a uniform slurry.
[0047] (6) Adding high alumina cement: During the slurry stirring process, add high alumina cement evenly and continue stirring for a period of time to ensure that the high alumina cement is fully dispersed and participates in the reaction.
[0048] (7) Molding: Pour the evenly stirred slurry into a pre-prepared mold, vibrate and compact it, remove bubbles, and shape the material.
[0049] (8) Curing: The molded material is placed at room temperature for curing for 1 day, then demolded and moved to a steam curing box for curing at 80°C for 2 days.
[0050] Since the preparation method of the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements has the same inventive concept as the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements, the preparation method of the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements has all the technical effects of the above-mentioned self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements, it will not be repeated here.
[0051] In the specific embodiment 1 of the present invention, the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided by the embodiment of the present invention includes the following components by weight: 22 parts of slag, 18 parts of fly ash, 7 parts of alkali activator, 10 parts of high-alumina cement (CA500-A700), 3 parts of polyethylene fiber, and 18 parts of water. The preparation method is as follows: First, the slag and fly ash are dried to remove moisture and impurities to ensure the purity and quality of the raw materials. The water glass solution is prepared 24 hours in advance to release heat. Then, the slag, fly ash and polyethylene fiber are mixed uniformly in proportion to obtain a solid mixture. The alkali activator is added to water to prepare a solution, and the solution is slowly added to the solid mixture, and stirred for 25 minutes to form a uniform slurry. Then, high-alumina cement is evenly added during the stirring of the slurry, and stirring is continued for 15 minutes. Afterwards, the slurry was poured into a mold, and the molded material was placed at room temperature for curing for 1 day, then demolded and moved to a steam curing box for curing at 80°C for 2 days to obtain a self-cleaning high-strength and high-toughness geopolymer material.
[0052] In the specific embodiment 2 of the present invention, the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided by the embodiment of the present invention includes the following components by weight: 20 parts of slag, 15 parts of fly ash, 6 parts of alkali activator, 8 parts of high-alumina cement (CA500-A700), 2 parts of polyethylene fiber, and 15 parts of water. The preparation method is as follows: First, the slag and fly ash are dried to remove moisture and impurities to ensure the purity and quality of the raw materials. The water glass solution is prepared 24 hours in advance to release heat. Then, the slag, fly ash and polyethylene fiber are mixed uniformly in proportion to obtain a solid mixture. The alkali activator is added to water to prepare a solution, and the solution is slowly added to the solid mixture, and stirred for 25 minutes to form a uniform slurry. Then, high-alumina cement is evenly added during the stirring of the slurry, and stirring is continued for 15 minutes. Afterwards, the slurry was poured into a mold, and the molded material was placed at room temperature for curing for 1 day, then demolded and moved to a steam curing box for curing at 80°C for 2 days to obtain a self-cleaning high-strength and high-toughness geopolymer material.
[0053] In the specific embodiment 3 of the present invention, the self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement provided by the embodiment of the present invention includes the following components by weight: 25 parts of slag, 20 parts of fly ash, 8 parts of alkali activator, 12 parts of high-alumina cement (CA500-A700), 5 parts of polyethylene fiber, and 20 parts of water. The preparation method is as follows: First, the slag and fly ash are dried to remove moisture and impurities to ensure the purity and quality of the raw materials. The water glass solution is prepared 24 hours in advance to release heat. Then, the slag, fly ash and polyethylene fiber are mixed uniformly in proportion to obtain a solid mixture. The alkali activator is added to water to prepare a solution, and the solution is slowly added to the solid mixture, and stirred for 25 minutes to form a uniform slurry. Then, high-alumina cement is evenly added during the stirring of the slurry, and stirring is continued for 15 minutes. Afterwards, the slurry was poured into a mold, and the molded material was placed at room temperature for curing for 1 day, then demolded and moved to a steam curing box for curing at 80°C for 2 days to obtain a self-cleaning high-strength and high-toughness geopolymer material.
[0054] In the specific comparative example 1 of the present invention, a geopolymer material is provided, and the geopolymer material includes the following components by weight: 22 parts of slag, 18 parts of fly ash, 7 parts of alkali activator, and 20 parts of water. The preparation method is as follows: First, the slag and fly ash are dried to remove moisture and impurities to ensure the purity and quality of the raw materials. The water glass solution is prepared 24 hours in advance to release heat. Then, the slag and fly ash are mixed evenly in proportion to obtain a solid mixture. The alkali activator is added to water to prepare a solution, and the solution is slowly added to the solid mixture, while stirring for 25 minutes to form a uniform slurry. Afterwards, the slurry is poured into a mold, and the molded material is placed at room temperature for curing for 1 day, and then demolded and moved to a steam curing box, and cured at 80°C for 2 days to obtain a geopolymer material.
[0055] In the specific comparative example 2 of the present invention, a geopolymer material is provided, and the geopolymer material includes the following components by weight: 22 parts of slag, 18 parts of fly ash, 7 parts of alkali activator, 3 parts of polyethylene fiber, and 20 parts of water. The preparation method is as follows: First, the slag and fly ash are dried to remove moisture and impurities to ensure the purity and quality of the raw materials. The water glass solution is prepared 24 hours in advance to release heat. Then, the slag, fly ash and polyethylene fiber are mixed evenly in proportion to obtain a solid mixture. The alkali activator is added to water to prepare a solution, and the solution is slowly added to the solid mixture, while stirring for 25 minutes to form a uniform slurry. Afterwards, the slurry is poured into a mold, and the molded material is placed at room temperature for curing for 1 day, and then demolded and moved to a steam curing box, and cured at 80°C for 2 days to obtain a geopolymer material.
[0056] The materials prepared in the above examples and comparative examples were subjected to performance tests, including compressive strength, tensile strength and tensile strain, self-cleaning effect and other indicators. The results are shown in the following table:
[0057]
[0058] It can be seen from the above test results that the embodiments of the present invention have excellent mechanical properties and self-cleaning effects. Therefore, the self-cleaning high-strength and high-toughness geopolymer material suitable for prefabricated pavements provided by the embodiments of the present invention has the following technical effects: (1) Realization of self-cleaning performance: By adding high-alumina cement to the material, zeolite with a porous structure is generated, thereby realizing the self-cleaning function of the pavement material, which provides a new idea and method for solving the dust pollution problem of prefabricated pavements. (2) Improvement of high-strength and high-toughness performance: By optimizing the ratio of raw materials and adding polyethylene fibers, the strength and toughness of the material are significantly improved, enabling it to better withstand the complex loads and environmental conditions faced by prefabricated pavements. (3) Expansion of application fields: The application of geopolymer materials to prefabricated pavements provides a new choice for the development of prefabricated pavement materials and promotes the advancement of prefabricated pavement technology.
[0059] In summary, the present invention aims to overcome the defects of existing prefabricated pavement materials and provide a self-cleaning high-strength and high-toughness geopolymer material with superior comprehensive performance. Specifically, the purposes of the invention include the following aspects: (1) Significantly improve the strength and toughness of prefabricated pavement materials to adapt to the increasing traffic load and reduce road damage and maintenance frequency. (2) Give the prefabricated pavement material a self-cleaning function, effectively absorb dust and dirt, keep the road clean and beautiful, and reduce cleaning costs. (3) Optimize the composition and preparation process of the material so that it has good construction performance and economic feasibility, so as to facilitate its wide application in actual engineering.
[0060] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0061] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement, characterized by: The invention is prepared from the following raw materials in parts by weight: 20-25 parts of slag, 15-20 parts of fly ash, 6-8 parts of alkali activator, 8-12 parts of high-alumina cement, 2-5 parts of polyethylene fiber and 15-20 parts of water.
2. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 1, characterized in that: The alkaline activator is selected from sodium hydroxide and water glass solution.
3. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 2, characterized in that: The purity of sodium hydroxide is not less than 96%.
4. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 2, characterized in that: The modulus of water glass solution is 1.5-3.
5.
5. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 1, characterized in that: The fly ash must have a fineness (residue on a 45 μm square sieve) of no more than 20% and a loss on ignition of no more than 8%.
6. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 1, characterized in that: The specific surface area of the slag is greater than 400m 2 / kg.
7. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 6, characterized in that: The activity index of the slag is not less than S95 grade.
8. The self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to claim 1, characterized in that: The high alumina cement model is CA500-A700, the initial setting time is no earlier than 30 minutes, and the final setting time is no later than 6 hours.
9. The self-cleaning high-strength and high-toughness geopolymer material suitable for fabricated pavement according to any one of claims 1 to 8, characterized in that: The polyethylene fiber has a length of 6-12 mm, a diameter of 20-40 μm, and a tensile strength of not less than 1000 MPa.
10. A method for preparing a self-cleaning high-strength and high-toughness geopolymer material suitable for assembled pavement according to any one of claims 1 to 9, characterized in that: (1) Raw material pretreatment: Dry the slag and fly ash separately to remove moisture and impurities to ensure the purity and quality of the raw materials; prepare the water glass solution 24 hours in advance to release heat; (2) Ingredients: accurately weigh slag, fly ash, alkali activator, high alumina cement and polyethylene fiber according to the above weight ratio; (3) Dry mixing: Put slag, fly ash and polyethylene fiber into a mixer, stir and mix them thoroughly to form a dry mix; (4) pulping: adding an alkali activator to an appropriate amount of water and stirring evenly to prepare an alkali activator solution; (5) Wet mixing: slowly add the prepared alkali activator solution into the dry mix while continuously stirring to fully wet the material and form a uniform slurry; (6) Adding high alumina cement: During the slurry stirring process, evenly add high alumina cement and continue stirring for a period of time to ensure that the high alumina cement is fully dispersed and participates in the reaction; (7) Molding: Pour the evenly stirred slurry into a pre-prepared mold, vibrate and compact it, remove bubbles, and shape the material; (8) Curing: The molded material is placed at room temperature for curing for 1 day, then demolded and moved to a steam curing box for curing at 80°C for 2 days.